In Search of a Better Outcome: Opting Into the Live Donor Paired Kidney Exchange Program. (May 2021) - Vinson, Amanda J.; Kiberd, Bryce A.; Tennankore, Karthik K.
Background: Live donor (LD) kidney transplantation is the best option for patients with end-stage kidney disease (ESKD). However, this may not be the best option if a patient's donor is older and considerably smaller in weight. Patient (A) with a less than ideal donor (Donor A) might enter into a live donor paired exchange (LDPE) program with the hopes of swapping for a better-quality organ. A second patient (B) who is in the LDPE may or may not benefit from this exchange with Donor A. Methods: This medical decision analysis examines the conditions that favor Patient A entering into the LDPE compared to directly accepting a kidney from their intended donor, as well as the circumstances where Patient B also benefits by accepting a lower-quality organ. Results: Under select circumstances, a paired exchange could benefit both Patients A and B. For example, a 30-year-old Patient A with a lower-quality donor might gain1.20 1.521.84 quality adjusted life years (QALYs) by entering into a LDPE for a better-quality kidney, whereas a 60-year-old Patient B might gain0.93 1.031.13 QALYs by accepting Donor A's kidney rather than waiting longer in the LDPE. The net benefit (or loss) of entering the LDPE differs by recipient age, donor organ quality, likelihood of Patient B being transplanted in LDPE, and likelihood of Patient A finding an ideal donor in the LDPE. Conclusion: This study shows there are ways to increase live donor utilization and effectiveness that require further research and potentially changes to the LDPE process.